Enterprise Applications and Services in the Finance Industry - Veit, Daniel J. (Springer, 2017)
The rapid development and adoption of technology-based information, communi- cation and product delivery systems have facilitated globalization of the financial services industry and removed the barriers between its vertical segments. New business and market models require the adaptation of existing IT infrastruc- tures as well as the development of innovative solutions for both experimental and operational systems.